The Implementation of E-Learning System on Intensive English Course in Darussalam Islamic Institution of Blokagung in Academic Year 2019/2020 - Fadilah, Laeliyatul; Dwi Andriani, Zulfi Zumala (IAI Darussalam, 2020)
This study explains about the implementation of the e-learning system on the Intensive English Course in IAI Darussalam in the academic year 2019/2020. There are three problem statements of this study that are How is the implementation and the problems of the implementation of e-learning systems in the intensive English course, the last is how are the students' responses to the implementation of the e-learning system in the intensive English course. This study used descriptive analysis. The findings of this study concluded that the most common problem in the implementation of the e-learning system in the Intensive English Course is an internet connection. The implementation of the e-learning system on the Intensive English course has a slightly positive and tends to be a negative response from the students. They fully need face-to-face learning with their tutors. They argue that the e-learning system is not more effective than learning an Intensive English Course that does it directly.